2005
DOI: 10.1159/000096833
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Predisposition to Asthma and Atopy

Abstract: A large number of studies have tried to identify heritable components in the susceptibility to asthma and atopy phenotypes. This review examines the evidence of multigenetic inheritance for these conditions. We identified in the literature at least 372 gene-disease association studies for asthma and 124 for atopy published in the last 6 years. Gene-environment analyses were performed in 41 and 14 articles, respectively, in the same time period. Many postulated associations have been probed with limited sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…A recent review of the literature revealed that five asthma candidate genes, ADAM33, TNF, TBXA2R, CD14 and LTC4S, were the focus of several meta-analyses in which ADAM33 and TNF had a modest association with asthma. 24 The first genome-wide replication study of 39 asthma candidate genes generated IL4RA results that were consistent with our observations. 25 In the most comprehensive replication study carried out to date, the reproducibility of 93 genes previously associated with asthma and/or asthma intermediate traits was tested.…”
Section: Discussionsupporting
confidence: 89%
“…A recent review of the literature revealed that five asthma candidate genes, ADAM33, TNF, TBXA2R, CD14 and LTC4S, were the focus of several meta-analyses in which ADAM33 and TNF had a modest association with asthma. 24 The first genome-wide replication study of 39 asthma candidate genes generated IL4RA results that were consistent with our observations. 25 In the most comprehensive replication study carried out to date, the reproducibility of 93 genes previously associated with asthma and/or asthma intermediate traits was tested.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, in pulmonary arterial hypertension there may be an interaction between fenfluramine exposure and genotype that influences disease development [48]. Other respiratory diseases thought to have multiple genetic influences on phenotype include asthma [49] and sarcoidosis [50]. If these genes have additive or synergistic effects, these are referred to as epistatic interactions.…”
Section: Genetic and Environmental Interactionsmentioning
confidence: 99%
“…It is characterised by obstruction of the airways of the lung and is related to atopy and bronchial hyperresponsiveness (BHR). Several chromosome regions and candidate genes have been associated with asthma, although the individual genes identified to date exhibit only modest effects and an unknown pattern of inheritance [1][2][3].…”
mentioning
confidence: 99%
“…It is located within the class III region of the major histocompatibility complex (MHC) region on chromosome 6p21.3 [5], which has previously been linked to asthma in various genome screens [1,3,6]. The TNF-a gene (TNFA) and lymphotoxin-a (LT-a) gene (LTA, also called TNFB) are members of the TNF superfamily.…”
mentioning
confidence: 99%